Rumors of War and Infernal Machines: Technomilitary Agenda-setting in American and British Speculative Fiction - Gannon, Charles E. (Rowman & Littlefield Publishers, 2005)
This provocative and unique work reveals the remarkably influential role of futuristic literature on contemporary political power in America. Tracing this phenomenon from its roots in Victorian Britain, Rumors of War and Infernal Machines offers a fascinating exploration of how fictional speculations on emergent or imaginary military technologies profoundly influence the political agendas and actions of modern superpower states. Gannon convincingly demonstrates that military fiction anticipated and even influenced the evolution of the tank, the development of the airplane, and also the bitter political battles within Britain's War Office and the Admiralty. In the United States, future-fictions and Cold-War thrillers were an officially acknowledged factor in the Pentagon's research and development agendas, and often gave rise_and shape_to the nation's strategic development of technologies as diverse as automation, atomic weaponry, aerospace vehicles, and the Strategic Defense Initiative ('Star Wars'). His book reveals a striking relationship between the increasing political influence of speculative military fiction and the parallel rise of superpower states and their technocentric ideologies. With its detailed political, historical, and literary analysis of U.S. and British fascination with hi-tech warfare, this lively and revealing study will appeal to students, literary and cultural scholars, military and history enthusiasts, and general readers.